Late Quaternary Pollen Records and Vegetation History of the Southwest Yukon Territory: A Review - Wang, Xia-Cheng; Geurts, Marie-Anne (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTThis paper is a summary of all known late Quaternary palynostratigraphic records from the southwest Yukon Territory. Thirty two pollen sites available by the end of 1988 are reviewed. Most pollen records in the region are of Holocene age. During the late-glacial to early Holocene, the southwest Yukon supported a herb-dominated tundra vegetation which was replaced by a birch-dominated shrub-tundra at about 10,000 yr BP. Spruce invaded the area between 9000 and 8600 yr BP at different localities, and a southward time transgression is visible in the Aishihik Basin. The current regional vegetation has been stable since 7600-8000 yr BP when dense spruce forest and/or spruce forest-tundra was established in most localities. In the Snag area, however, dense spruce forest developed only around 5700 yr BP, which is about 2000 years later than in the Aishihik Basin. The exotic pine pollen records in the region exhibit an interesting pattern, suggesting a frequent shift of the atmospheric circulation system. Anomalous records of alder pollen from the Aishihik Basin and adjacent regions suggest that alder has never been widespread in these areas due to aridity, and alder pollen is greatly overrepresented in pollen spectra. Spruce arrival dates suggest that further investigations in the Tintina Valley, Yukon River Valley, and Car-macks region might provide useful information concerning the spruce migration routes.